Doubts about the Strength of Financial Intelligence Documents as Evidence in Money Laundering Crimes - Ade Putra R; Yuliati Yuliati; Yenny Etta Widyanti; Milda Istiqomah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2026)
Based on the principle of legality, valid evidence in handling money laundering cases in Indonesia is one of them in the form of documents. The financial intelligence document issued by the Financial Intelligence Unit (FIU) is one of the documents that has been regulated in the provisions of the legislation which is a valid evidence. Recently, cases of Money Laundering Crimes (TPPU) that have occurred in Indonesia, such as cases involving insurance corporations, namely the case of PT Jiwasraya Insurance and PT Asabri Insurance, which used the capital market as a means to launder money from the predicate crime. This study aims to demonstrate by explaining the valid evidence in handling money laundering cases in Indonesia. The method used is normative juridical based on legal analysis and cases, this study found legal ambiguity related to the provisions of Article 73 of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes (PPTPPU Law). This study provides the conclusion that the harmonization of regulations that are open to multiple interpretations is needed so that law enforcement officers do not hesitate in applying these rules.